Redução de bactérias gram negativas em camas de aviário tratadas com lona na superfície e gás amônia - Muniz, Richard Francisco (2020)
The reuse of poultry litter is a common practice in the production of broilers in Brazil. This practice significantly reduces the cost of production and contributes to the preservation of the environment. However, this handling in the litter can transmit from one batch to another microorganisms, such as Salmonellas, which are harmful to the health of birds and humans. Current methods of disinfecting bedding (adding lime, shallow fermentation and windrowing) do not guarantee the elimination of pathogenic microorganisms. The tarpaulin on the surface method has shown, compared to other methods, greater effectiveness in reducing pathogenic microorganisms because it generates an increase in the ammonia gas in the bed when covered by a tarpaulin over a period of 08 days. However, the low amount of ammonia gas produced by bacterial fermentation does not guarantee the disinfection of the bed. The objective of this work was to compare the shallow fermentation (T1) and shallow fermentation with injection of 0.22% ammonia gas (T2), using the Aveclean® applicator, and to verify the effectiveness of the Aveclean® system in field conditions, evaluating the reduction of Gram negative bacteria in reused aviary beds. The T2 treatment and the field experiment significantly reduced Gram negative bacteria in the avian litter, while the T1 treatment was not effective in the evaluated period of 48 hours. In this way, the improvement of the shallow fermentation with the injection of 0.22% of ammonia gas, using the Aveclean® system proved to be efficient in the control of Gram negative microorganisms in poultry beds.